The Impact of Full-Length, Trimeric and Globular Adiponectin on Lipolysis in Subcutaneous and Visceral Adipocytes of Obese and Non-Obese Women - Wedellova, Zuzana; Kovacova, Zuzana; Tencerova, Michaela; Vedral, Tomas; Rossmeislova, Lenka; Siklova-Vitkova, Michaela; Stich, Vladimir; Polak, Jan (PloS one, 2013)
Contribution of individual adiponectin isoforms to lipolysis regulation remains unknown. We investigated the impact of full-length, trimeric and globular adiponectin isoforms on spontaneous lipolysis in subcutaneous abdominal (SCAAT) and visceral adipose tissues (VAT) of obese and non-obese subjects. Furthermore, we explored the role of AMPK (5'-AMP-activated protein kinase) in adiponectin-dependent lipolysis regulation and expression of adiponectin receptors type 1 and 2 (AdipoR1 and AdipoR2) in SCAAT and VAT. Primary adipocytes isolated from SCAAT and VAT of obese and non-obese women were incubated with 20 µg/ml of: A) full-length adiponectin (physiological mixture of all adiponectin isoforms), B) trimeric adiponectin isoform or C) globular adiponectin isoform. Glycerol released into media was used as a marker of lipolysis. While full-length adiponectin inhibited lipolysis by 22% in non-obese SCAAT, globular isoform inhibited lipolysis by 27% in obese SCAAT. No effect of either isoform was detected in non-obese VAT, however trimeric isoform inhibited lipolysis by 21% in obese VAT (all p<0.05). Trimeric isoform induced Thr172 p-AMPK in differentiated preadipocytes from a non-obese donor, while globular isoform induced Ser79 p-ACC by 32% (p<0.05) and Ser565 p-HSL by 52% (p = 0.08) in differentiated preadipocytes from an obese donor. AdipoR2 expression was 17% and 37% higher than AdipoR1 in SCAAT of obese and non-obese groups and by 23% higher in VAT of obese subjects (all p<0.05). In conclusion, the anti-lipolytic effect of adiponectin isoforms is modified with obesity: while full-length adiponectin exerts anti-lipolytic action in non-obese SCAAT, globular and trimeric isoforms show anti-lipolytic activity in obese SCAAT and VAT, respectively.
Keywords: Protein Isoforms; Adipocytes; Protein Multimerization; kultivované buňky; multimerizace proteinu; tukové buňky; Real-Time Polymerase Chain Reaction; Subcutaneous Fat; Obesity; nitrobřišní tuk; ribonukleotidy; adiponektin; Adiponectin; podkožní tuk; Middle Aged; Aminoimidazole Carboxamide; Adult; proteinkinasy aktivované AMP; Lipolysis; hypoglykemika; kvantitativní polymerázová řetězová reakce; Cells, Cultured; receptory adiponektinu; aminoimidazolkarboxamid; ženské pohlaví; Gene Expression; protein - isoformy; Humans; Intra-Abdominal Fat; Receptors, Adiponectin; AMP-Activated Protein Kinases; lidé středního věku; obezita; exprese genu; Ribonucleotides; dospělí; Female; Hypoglycemic Agents; lipolýza; lidé